Pathological functions of interleukin‐22 in chronic liver inflammation and fibrosis with hepatitis B virus infection by promoting T helper 17 cell recruitment. Issue 4 (1st March 2014) - Zhao, Juanjuan; Zhang, Zheng; Luan, Yan; Zou, Zhengsheng; Sun, Yanling; Li, Yonggang; Jin, Lei; Zhou, Chunbao; Fu, Junliang; Gao, Bin; Fu, Yangxin; Wang, Fu‐Sheng
<x xml:space="preserve">Abstract</x> It is well established that interleukin (IL)‐22 has hepatoprotective and antifibrotic functions in acute liver injury models; however, its function in patients with liver fibrosis and liver cirrhosis (LC) remains obscure. In the current study, we demonstrated that expression of numerous IL‐22 pathway‐associated genes was significantly up‐regulated in hepatitis B virus (HBV)‐infected liver tissues, compared to normal controls, through microarray analysis. In agreement with these findings, liver‐infiltrating IL‐22+ cells were largely increased in HBV‐infected patients with LC, compared to those without LC or healthy subjects, and were positively associated with liver fibrosis staging scores. Immunohistochemistry and flow cytometric analyses revealed that IL‐22 was produced by multiple intrahepatic immune cells and, preferentially, by T‐helper (Th) 17 cells in LC patients. In an HBV transgenic (Tg) mouse model of T‐cell‐mediated chronic liver inflammation and fibrosis, blockade of IL‐22 attenuated hepatic expression of chemokine (C‐X‐C motif) ligand 10 and chemokine (C‐C motif) ligand 20 (CCL20) and subsequently reduced Th17 recruitment and liver inflammation and fibrosis progression. In vitro treatment with IL‐22 stimulated hepatic stellate cells (HSCs) to secrete several chemokines and subsequently promoted Th17 cell chemotaxis. Blocking C‐X‐C chemokine receptor type 3 or CCL20 reduced Th17 cell chemotaxis by IL‐22‐treated HSCs. Conclusions: IL‐22 plays a pathological role in exacerbating chronic liver inflammation and fibrosis by recruiting hepatic Th17 cells in HBV‐infected patients and HBV Tg mice. (Hepatology 2014;59:1331‐1342)